A Family Study of Adult Twins with and without a History of Childhood Abuse: Stability of Retrospective Reports of Maltreatment and Associated Family Measures - Nelson, Elliot C. (2010)
Childhood sexual abuse (CSA) and physical abuse (CPA) are well-established risk-factors for a wide of range of proximal and distal outcomes. The lack of availability of an optimal design for examining abuse and its consequences has resulted in the use of various approaches, each having its own limitations. We describe the Childhood Trauma Study which ascertained families from a large young adult Australian twin cohort on the basis of twins’ responses to screening questions assessing CSA and CPA. We report data from 3407 participants including twins, non-twin siblings, and their parents. Our data demonstrate the feasibility of using a comprehensive assessment to evaluate retrospective history of childhood abuse in an adult sample. We observed that risk for each form of abuse increased incrementally with the number of parents with alcohol problems. Psychometric properties of our measures of CSA and CPA including reasonable long-term stability, construct validity, and evidence of familial corroboration compare favorably with those of other reports in which samples were considerably younger and assessments were repeated over shorter intervals.